ANALYSIS OF COMPETITIVENESS SMI BATIK IN BOGOR CITY - Defytri Nur Agustine; Nikensari, Sri Indah; Sariwulan, Rd. Tuty (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This study aims to identify and analyze the competitiveness of batik SMEs in Bogor City. Data were obtained from interviews with 3 batik SMEs in Bogor City using descriptive qualitative methods using SWOT analysis. The results of this study indicate that if you carry out a strategy carried out by each SMI using the SO strategy, that is a strategy that uses strength to take advantage of the opportunities that exist in each IKM in the city of Bogor.